2015
DOI: 10.2174/1874364101509010156
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Pain in Oculoplastic Procedures by Reducing the Rate of Injection of Local Anaesthetic

Abstract: Purpose :To investigate whether the rate of infiltration of local anaesthetic influences the pain or efficacy of local anaesthesia in oculoplastic surgery.Methods :A prospective observational study on consecutive patients undergoing a variety of oculoplastic procedures under local anaesthesia. An observer recorded the rate of injection of local anaesthetic during each procedure. The same mixture of local anaesthetic and the same needle gauge was used in all cases. Patients were asked to rate the pain of both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Pain is a complex and subjective sensation that is influenced by various factors as patients can experience varying degrees and forms of pain [ 1 , 3 ]. There are various techniques that can help alleviate the discomfort caused by injection pain, including the utilization of multiple forms of sensory noise, administering the needle perpendicularly, opting for a smaller needle, or gradually decreasing the injection rate [ 4 , 5 , 10 ]. However, previous attempts have focused on changing the technique and we have tried to change the tools used for anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain is a complex and subjective sensation that is influenced by various factors as patients can experience varying degrees and forms of pain [ 1 , 3 ]. There are various techniques that can help alleviate the discomfort caused by injection pain, including the utilization of multiple forms of sensory noise, administering the needle perpendicularly, opting for a smaller needle, or gradually decreasing the injection rate [ 4 , 5 , 10 ]. However, previous attempts have focused on changing the technique and we have tried to change the tools used for anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…When anesthesia is first injected, a high pressure needs to be quickly injected to overcome tissue resistance, causing severe pain to patients. If the anesthesia is injected slowly, the tissue will expand slowly, reducing the pain [5], but the total time required for anesthesia may increase, potentially leading to an increase in pain perceived by the patient. NPRS is an effective and valid tool for measuring pain in many areas [11], including excision surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that slower injection speed is associated with less patient discomfort. 55 Once the tract is fully anesthetized, the access needle can be advanced through the “cylinder of local anesthetic” into the target of choice ( Fig. 1 ).…”
Section: Practical Application—the Authors' Practicementioning
confidence: 99%
“…It is widely recommended that anesthetic injections should be administered slowly in the eyelid to decrease discomfort 27. The slow administration of lidocaine may have a greater impact on decreasing perceived pain than buffered lidocaine 58.…”
Section: Preparation and Administration Of Local Anestheticmentioning
confidence: 99%